Effects of drought on nitrogen uptake and carbon dynamics in trees. (4th November 2020) - Joseph, Jobin; Luster, Jörg; Bottero, Alessandra; Buser, Nathalie; Baechli, Lukas; Sever, Krunoslav; Gessler, Arthur
Abstract: Research on drought impact on tree functioning is focussed primarily on water and carbon (C) dynamics. Changes in nutrient uptake might also affect tree performance under drought and there is a need to explore underlying mechanisms. We investigated effects of drought on (a) in situ nitrogen (N) uptake, accounting for both, N availability to fine roots in soil and actual N uptake, (b) physiological N uptake capacity of roots and (c) the availability of new assimilates to fine roots influencing the N uptake capacity using 15 N and 13 C labelling. We assessed saplings of six different tree species ( Acer pseudoplatanus L., Fagus sylvatica L., Quercus petraea (Mattuschka) Liebl., Abies alba Mill., Picea abies (L.) H.Karst. and Pinus sylvestris L. ). Drought resulted in significant reduction of in situ soil N uptake in deciduous trees accompanied by reduced C allocation to roots and by a reduction in root biomass available for N uptake. Although physiological root N uptake capacity was not affected by drought in deciduous saplings, reduced maximum ammonium but not nitrate uptake was observed for A. alba and P. abies . Our results indicate that drought has species-specific effects on N uptake. Even water limitations of only 5 weeks as assessed here can decrease whole-plant inorganic N uptake, independent of whether the physiological N uptake capacity is affected or not.